(untitled) (Jurnal Teknologi (Sciences & Engineering), 2014)
Semi-SWATH ship has a different characteristics compared to the common ship hull. The ship has a tendency to suffer bow-dive due to low restoring force at bow when running in following seas. In some conditions, the foredeck found to be immersed under the rear of wave. Acceleration motion to the trough increases the momentum force that pushing the ship to dive. The condition may cause the ship has a loss of control even the crew can feel thrown forward. In this research, fin stabilizer was applied to reduce the effect of those conditions with application of fuzzy logic controller. The controller calculates the angle for the fin stabilizer based on the pitch angle. The fin at both ends of the ship’s hull increase the lift force, reduce the trim angle, and restrain the ship from dynamic high acceleration. A numeric time-domain program developed to analyze the ship seakeeping in following sea. The results showed the controller ofthe fin stabilizer has a significant effect in preventing the ship from the unsafe condition.